2001
DOI: 10.1016/s0008-6363(00)00259-5
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and calcium current blocking properties of the novel antiarrhythmic agent H 345/52: implications for proarrhythmic potential

Abstract: H 345/52 blocks I(Kr) with high potency and I(Ca) with somewhat lower potency and was found to delay ventricular repolarisation without substantially increasing temporal or spatial dispersion and without inducing early after-depolarisations or TdP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…highly proarrhythmic whereas combined ion channel blockers, as exemplified by H 345/52, AZD7009 and vernakalant, did not express TdP. 9,10,17,18 The outcome is also in accordance with proarrhythmia studies in which selective IKr blockers were combined with either calcium-or sodium-channel blocking drugs and found to dramatically reduce the incidence of TdP as compared to when the IKr blocker was administered solely. 19,20 Interestingly, in the latter studies the low incidence of the combination was obvious despite similar degrees of repolarization delay (ie, QT or JT prolongation) as those induced by the IKr blocker alone.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…highly proarrhythmic whereas combined ion channel blockers, as exemplified by H 345/52, AZD7009 and vernakalant, did not express TdP. 9,10,17,18 The outcome is also in accordance with proarrhythmia studies in which selective IKr blockers were combined with either calcium-or sodium-channel blocking drugs and found to dramatically reduce the incidence of TdP as compared to when the IKr blocker was administered solely. 19,20 Interestingly, in the latter studies the low incidence of the combination was obvious despite similar degrees of repolarization delay (ie, QT or JT prolongation) as those induced by the IKr blocker alone.…”
Section: Discussionsupporting
confidence: 67%
“…32 Likewise, inhibition of inward calcium currents during concomitant IKr blockade would result in reduced proclivity towards repolarization-related proarrhythmias as experimentally demonstrated for several combined potassium and calcium-channel blocking antiarrhythmic drugs. 17,[33][34][35] Interestingly, Huang and others proposed that the low proarrhythmic potential of CPU228, a dofetilide analogue, could be ascribed to its calcium-blocking properties. 34 Although the present proarrhythmia model critically relies on a 1 -adrenoceptor stimulation for TdP induction, it is most unlikely that a 1 -adrenoceptor blockade underlies the low proarrhythmic potential of AZD1305 as the IC 50 value for such blockade is above 100 mmol/L (AstraZeneca, data on file).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the antiarrhythmic agent H 345/52, inhibition of ICa L in isolated rabbit cardiomyocytes was dependent upon frequency and membrane potential, with a large inhibition at higher frequencies and depolarised potentials (Amos et al, 2001). If such a frequency-and state-dependence of the block is also present in the case of AZD7009, the contribution of the inhibition of ICa L may be substantial.…”
Section: Mechanisms Underlying the Low Proarrhythmic Potential Of Azdmentioning
confidence: 99%
“…Consequently, the search for new types of antiarrhythmic drug to treat malignant cardiac arrhythmias remains an important area of research (Sanguinetti and Bennett, 2003). Recently, much attention has been focused on the antiarrhythmic drugs with multiple modes of action (i.e., acting on different ion channels and/or receptors), with the expectation that such agents may be more effective for therapy and devoid of serious cardiac side effects (Má tyus et al, 1997;Amos et al, 2001).…”
mentioning
confidence: 99%
“…The modest positive inotropy by HA-7 may be viewed as a potential therapeutic advantage over d-sotalol and other similar cardiodepressant agents. Furthermore, it has been suggested that the block of I Ca and/or I Na , by reducing the risk of early after-depolarization development with excessive APD prolongation, attenuating excessive repolarization delay and temporal dispersion of repolarization may contribute to the reduced proarrhythmic potential of the multiple channel blockers (Abrahamsson et al, 1996;Amos et al, 2001). Consequently, because of its multifaceted actions, it can be reasonably expected that HA-7 may possess promising antiarrhythmic efficacy but lesser or negligible proarrhythmic risk.…”
mentioning
confidence: 99%